Application Of Drawing Time For School Phobia At The Beginning Of School Entry For Preschool Children - Salsabila Hasiana Tanjung (Universitas Negeri Medan, 2017)
School phobia is often experienced by preschool children at the beginning of school entry. The child's fear is caused by the child has not felt comfortable and safe with his or her new environment or can be caused by the child is not familiar with the immediate environment as with his family. School phobias can occur up to three days, one week even to mid-semester. Child's fear can be expressed by nailing his body when they are about to enter the school, hiding behind the body that leads to school, crying, shouting and giving reasons to be out of school or to be kept by his parents or those who deliver the children to school. Children who experience school phobia need social and emotional development so that children feel comfortable and safe in school. The social and emotional development of children is derived from the maturity and learning opportunities of various environmental responses to children. Optimal social development is derived from healthy social responses and opportunities given to children to develop positive self- concept. Through drawing activities between children and teachers, children can develop their interests and attitudes and approach to new environments in their school. This article discusses the activities of